Crystal structure of (E)-1-(5-bromo-2-hydroxyphenyl)-3-(5-(4-methoxyphenoxy)-3-methyl-1-phenyl-1H-pyrazol-4-yl)prop-2-en-1-one, C26H21BrN2O4 - Shin Soon Young; Lee Ha-Jin; Koh Dongsoo (Zeitschrift für Kristallographie - New Crystal Structures)
C26H21BrN2O4, triclinic, P1̄ (no. 2), a = 9.061(3) Å, b = 11.640(3) Å, c = 12.751(3) Å, α = 65.985(7)°, β = 87.683(8)°, γ = 72.332(12)°, V = 1165.1(5) Å3, Z = 2, R gt(F) = 0.0351, wR ref(F 2) = 0.0873, T = 296(2) K.